Sellar and parasellar lesions: a pictorial illustration - Hassan, Radhiana; Mohamad Mukari, Shahizon Azura; Sharis Osman, Syazarina; Hashim , Hilwati; Muda, Ahmad Sobri (2013)
Learning Objective: To present imaging characteristics of various common and uncommon Sellar and Parasellar lesions. Brief Content: The Sella Turcica and adjacent area is a small but complex part of the central nervous system. It contains many structures that can give rise to myriad of pathological lesion. This pictorial exhibit will review common and some uncommon types of pathological processes that occur in this region. Some of the lesions that will be displayed will include: Pituitary Microadenoma, Macroadenoma, Pituitary Apoplexy, Rathke cleft cyst, empty Sella, Aneurysms, Epidermoid/Dermoid, Metastases, Craniopharyngioma, Germinoma, Arachnoid Cyst, Tuber Cinerium Hamartoma, Chiasmatic Glioma, , Lymphocytic Hypophysitis, and Infundibular Histiocytosis